Restructuring Uganda’s Coffee Industry : Why Going Back to the Basics Matters - Baffes, John (World Bank, Washington, DC, 2012)
Uganda's coffee industry consists of low input-intensity smallholders with an average farm size of 0.2 hectares and is the main source of income for an estimated 500,000 households. Following its introduction earlier in the 20th century, the industry expanded considerably during the 1950s and 1960s. However, the sector experienced a huge setback due to the civil strife of the 1970s, when output halved within a 5-year period (1972-77). During the late 1980s, the sector went through a liberalization process, which, coupled with high world prices, led to considerable supply response, with exports exceeding 4 million bags in two consecutive years (1995 and 1996), the only time in the sector's history. By all accounts, the reforms have been successful. Producers' share of export prices doubled and growers receive payments promptly. Entrepreneurial activity has increased enormously. Most important, there has been a well documented poverty reduction impact on households of the coffee growing regions. There has been no backtracking of reforms.